Islamic Economic Ethics in the Age of Technological Disruption: Redefining Industrial Growth for the Common Good - Muthi' 'Adilah Bahril; Sekar Mayang; Anugrah Mustika Putri Puspitasari; Ucu Musahidah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose: This study investigates how Islamic economic ethics serves as a moral and strategic framework addressing technological disruption challenges in the Fourth Industrial Revolution (IR4.0), focusing on redefining industrial growth for the common good (maslahah).Design/Methodology: A Systematic Literature Review (SLR) was conducted using the PRISMA approach. Data were retrieved from Scopus and complementary databases using keywords on Islamic economic ethics, technological disruption, and industrial growth. After screening, 48 peer-reviewed articles were selected. Bibliometric analysis was performed using Biblioshiny (bibliometrix R-package) to extract quantitative metadata.Findings: The review identifies three main research streams: (1) applying maqasid al-shariah to ethical evaluation of emerging technologies (41.7%), (2) developing normative Islamic ethics models as Western alternatives (31.2%), and (3) linking Islamic values with sustainability and inclusive industrial growth (27.1%). Bibliometric data reveal 66.7% of studies are conceptual, versus 33.3% empirical. Geographically, Malaysia (37.8%) and Indonesia (27.8%) dominate the literature.Practical Implications: Strengthening the integration of Islamic ethics into technology governance and industrial policy promotes socially responsible, sustainable, and Shariah-compliant innovation. Recommendations include establishing AI Ethics Subcommittees within National Shariah Boards and adopting Shariah-by-Design protocols for Islamic FinTech developers.Originality/Value: This systematic review connects Islamic economic ethics with technological disruption, offering conceptual insights and directions for future interdisciplinary research. The primary theoretical contribution is the synthesis of the Islamic Ethical Technology Governance Model (IETGM).